X-ray crystallographic fragment screening against the human prion protein - Rangel, Victor Lopes (2021)
Prion diseases result from the ordered accumulation of the misfolded conformer of cellular prion protein (PrPC), a glycosyl-phosphatidylinositol (GPI)-anchored protein expressed on the cell surface. The critical event in prion diseases is the conversion of PrPC into the self-propagating conformer scrapie prion protein, PrPSc, with resultant propagation and accumulation resulting in neuronal death and amyloidogenesis. Prognoses are devastating, with an average survival time of approximately one year after the onset of symptoms. Despite the tremendous efforts, PrP physiological function and its mechanism of conversion to PrPSc remain elusive. This research focuses on Xray crystallographic fragment screening technique to map PrP chemical spaces in order to find lead compounds as part of the drug discovery process. Screening against human PrP, currently stigmatized as an \"undruggable\" target, can benefit from the fragment screening strategy. This approach relies on low molecular weight compounds to scan the protein surface in search of binding spots in the protein, enhancing the chances of finding ligands that could offer an alternative route to quest a treatment to prion disease. Any hits could be explored to be used for either i) increase PrPC stabilization, increasing the energy barrier for the protein conversion, ii) destabilization, to induce PrP removal from the cell, thus reducing the quantity of PrP available for conversion, or iii) block protein-protein interaction sites between PrPC and PrPSc , inhibiting the conversion process. We have established a reproducible crystal system for which we collected over 1000 X-ray datasets and screened over 600 fragments. Our data shows two ligands interacting with the prion protein and reveal a pyrazole chemical binding motif for an unprecedented small cavity created by a conformational change of the Lys185 sidechain. The in silico analysis of the collected datasets showed that the globular domain of the PrP is unexpectedly rigid. To overcome the difficulty of finding PrP binder molecules, we performed a second fragment screening assay. The second screening was enabled by achieving a more fragment screening-friendly crystal. This search involved screening for a new crystal system, the use of a PrPspecific nanobody, and PEG-based conditions. Our second screening tested over 100 fragments, with no hits. Together, we believe that our work has the potential to provide structural basis to aid the drug discovery regarding the prion protein while also providing an in-depth analysis that can support other X-ray fragment screening endeavors.